Pendidikan Berbasis Komunitas: Membangun Ekonomi Kerakyatan Melalui Keterlibatan Masyarakat - Moh. Wahib; Ari Susanto (PUTRA JAWA PUBLISHER, 2024)
This paper will highlight the importance of community involvement in education processes and local economic development. By analyzing various initiatives that actively involve communities, this article will show how education can be a key driver in creating sustainable and inclusive economic opportunities. Community-based education plays an important role in building a popular economy through active community involvement in the education process. This research examines how community-based education programs can strengthen local economies by improving community skills, facilitating social participation, and creating collective awareness about the potential of local resources. Using qualitative methods through in-depth interviews with resource persons, such as village heads, local economic activists and academics in the field of community development, this study found that community-based education not only provides practical skills but also strengthens social networks that encourage sustainable economic development. The article suggests that collaboration between communities, local governments and educational institutions can increase the effectiveness of programs in empowering communities and building resilient economies.